Project management: engineering’s key weapon to boost development - GOMEZ SANCHEZ SOTO, RUBEN (LACCEI, 2025)
Abstract–This paper explores the critical importance of project management skills for engineers and their impact on national development. The benefits of implementing project management practices are discussed, as well as the risks and negative consequences that arise when engineers lack these competencies. Using data from the Project Management Institute (PMI) Pulse of the Profession reports from 2017, 2018, and 2019, quantitative evidence is presented on how project management improves organizational performance, reduces resource waste, and increases project success rates. The results show that organizations with high project management maturity waste up to 28 times less money than low-performing ones, and that up to 69% of projects meet their original objectives when good practices are implemented. The symbiotic relationship between engineering, project management, and national development is also examined, highlighting how these disciplines interconnect to drive socioeconomic growth. The paper concludes by emphasizing the need to integrate project management skills into engineering training and practice to maximize their contribution to the sustainable development of countries.